1989
DOI: 10.1007/bf02248670
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory hypoactivity induced by m-trifluoromethylphenylpiperazine (TFMPP) and m-chlorophenylpiperazine (m-CPP)

Abstract: The action of m-trifluoromethylphenylpiperazine (TFMPP) and m-chlorophenylpiperazine (m-CPP), inhibiting the exploratory activity (ambulation and peeping) of the rat was studied in the open field test. The effects of both these drugs were antagonized by mesulergine, metergoline and mianserin, and partly by methysergide. Spiperone showed an antagonistic action in one (mean) dose only. The effects of TFMPP and m-CPP were not antagonized by ipsapirone, gepirone, cyanopindolol, compound 21009, cyproheptadine, rita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 14 publications
4
17
0
Order By: Relevance
“…The animals were then placed into 30 ϫ 30 cm 2 Plexiglas chambers for 15 min and changes in the animals' behavior were monitored to allow for observation of any changes in behavior produced by the pretreatment compound alone. Previous studies have shown that 15 min was sufficient to allow for maximum behavioral and/or biochemical effects of the compounds tested (3,9,10). In addition, our behavioral observations indicated that 15 min was sufficient time to observe behavioral effects of these compounds.…”
Section: Behavioral Observationssupporting
confidence: 65%
“…The animals were then placed into 30 ϫ 30 cm 2 Plexiglas chambers for 15 min and changes in the animals' behavior were monitored to allow for observation of any changes in behavior produced by the pretreatment compound alone. Previous studies have shown that 15 min was sufficient to allow for maximum behavioral and/or biochemical effects of the compounds tested (3,9,10). In addition, our behavioral observations indicated that 15 min was sufficient time to observe behavioral effects of these compounds.…”
Section: Behavioral Observationssupporting
confidence: 65%
“…The exploratory hypoactivity induced by m-CPP is considered to be mediated by 5-HTlc receptors (Kennett and Curzon, 1988;Ktodzifiska et al, 1989). Both sertraline and citalopram given repeatedly inhibited that effect, which may indicate that the sensitivity of 5-HTlc receptors decreases.…”
Section: Discussionmentioning
confidence: 95%
“…Mesulergine, ritanserin, and ketanserin, in a range of doses similar to those used in our experiments, attenuated or even completely blocked the anorexia induced by TFMPP in freely feeding rats, an effect in which 5-HT1, andfor 5-HT2 receptors are involved (Klodzinska and Chojnacka-Wojcik, 1990). Moreover, mesulergine, but not ritanserin, administered at the same doses used in this study, antagonized TFMPP-induced hypoactivity in rats, an effect mediated by 5-HT1, receptors (Klodzinska et al, 1989). On the other hand, only high doses of spiperone, such as those necessary to block the anticonvulsant effect of TFMPP, were reported to antagonize TFMPP-induced hyperthermia in heatadapted rats, a response mediated mainly by 5-HT2 receptors (Klodzinska and Chojnacka-Wojcik, 1992).…”
Section: Discussionmentioning
confidence: 48%